AGRICULTURE SHARIA CONTRACT BASIS: ANALYZING THE PRACTICE OF MUZARAH IN PINRANG SOUTH SULAWESI - Ulfa Hidayati Ulfa (Fakultas Syariah Institut Agama Islam Negeri Palu, 2021)
This research aims to provide information and input to the community in carrying out economic activities, especially the community in Tiroang.This research uses qualitative research with method approaches, observations, interviews, documentation, and literature studies.The data analysis technique used is triangulation. The results of this study show that. 1) The form of agricultural land cultivation agreement through a system of cooperation followed by a revenue sharing system is not made in written form because it still uses custom, where the landowner gives up his land or land to be tilled by others.using the provisions of the revenue sharing system. 2) The form of capital in the form of seeds and loss costs; If agricultural land fails to harvest, landowners jointly bear certain losses in the form of pesticides and fertilizers and the rest is borne by landholders.3) A review of Islamic law on the cultivation of agricultural land in the Tiroang community is allowed syar'i because it follows the system of agricultural cooperation known in Islam, namely the muzara'ah system.